The evolution of sperm competition genes: the effect of mating system on levels of genetic variation within and between species - Dapper, Amy L. (Evolution, 2016)
It is widely established that proteins involved in reproduction diverge between species more quickly than other proteins. For male sperm proteins, rapid divergence is believed to be caused by post-copulatory sexual selection and/or sexual conflict. Here, we derive the expected levels of gene diversity within populations and divergence between them for male sperm protein genes evolving by post-copulatory, pre-zygotic fertility competition, i.e. the function imputed for some sperm and seminal fluid genes. We find that, at the mutation-selection equilibrium, both gene diversity within species and divergence between them are elevated relative to genes with similar selection coefficients expressed by both sexes. We show that their expected level of diversity is a function of the harmonic mean number of mates per female which affects the strength of fertility selection stemming from male-male sperm competition. Our predictions provide a null hypothesis for distinguishing between other selective hypotheses accounting for the rapid evolution of male reproductive genes.